Veto-Based Delegation - Tymofiy Mylovanov (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
In a principal-agent model with hidden information and no monetary transfers, I establish the Veto-Power Principle: any incentive-compatible outcome can be implemented through veto-based delegation with an endogenously chosen default decision. This result demonstrates the exact nature of commitment powers required by the principal: (1) to design the default outcome and (2) to ensure that she has almost no formal control over the agent's decisions.
urn:nbn:de:bvb:19-epub-13422-3
Keywords: D78; D82; L22; M54; 330; veto power; asymmetric information; principal-agent relationship; no monetary transfers